(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT This study highlights the significance of language and its influence on the human psyche. It underscores the importance of respecting parents and refraining from using derogatory language towards them. The term "f" encompasses various negative connotations, thus it serves as a warning against verbal abuse towards parents. It is imperative to show reverence towards parents and avoid causing them any offense. This study affirms the significance of each word in the Holy Qur’an. Specifically, the verses in Surat al-Isra’ and al-Ahqaf that mention the word “f” highlight the potential consequences of disrespecting one’s parents, which is considered a major sin requiring repentance for forgiveness. The use of the small word “f” serves as evidence of disobedience towards parents and may lead to punishment in the afterlife. The research revealed that the letter "F" in Surat Al-Anbiya signifies the significant historical event of disproving the divinity of idols during the time of Prophet Abraham. This event emphasizes the belief in the singular and supreme nature of God. The word "F" represents the courage displayed by Prophet Ibrahim in confronting the oppressive leaders of his community.